Evaluation The Accuracy Of Surveying Data Of The Mobile Topographer Application On Smartphone - محفوض ندى; بوبو معن (Latakia University Journal -Engineering Sciences Series, 2020)
Positioning using global navigation satellite systems is one of the advantages available in smart phones running Android system, where the accuracy of positioning reached more than half a meter due to the development of the phone chips for these systems, and also as a result of the development of related software applications. The accuracy of each of the following was assessed by Mobile Topographer Application : Syrian horizontal stereographic coordinates after calibration of the application on one of the points known coordinates. Orthometric height that is not calibrated within this application and propose a mechanism for calibration. The area and perimeter of polygon which observed in this application. The results are presented in tables and charts, and indicated the possibility of using the application after calibration in GIS and real estate works as a calculation of area and perimeter.